The Effect of Sustainability Report Disclosure on Financial Company Performance - Ago Rival Pramono; Jawoto Nusantoro; Gustin Padwa Sari (Syntax Literate, 2023)
This study aims to examine the Effect of Sustainability Report Disclosure on the Company's Financial Performance. This study uses a quantitative descriptive research method. The data used in this research is secondary data. The population in this study are companies listed in the LQ45 index and listed on the Indonesia Stock Exchange, which reached 45. The data analysis technique used was multiple linear regression and was carried out with the help of IBM SPSS Version 21.0. The results show that the Sustainability Report has an effect on the Company's Financial Performance, namely Environmental Performance has a negative effect, Social Performance has a positive effect and Economic Performance has a positive effect. The research is limited to companies listed on the LQ45 Index of the Indonesia Stock Exchange from 2017 to 2019 and only focuses on the Company's Financial Performance Sustainability Report. Companies listed on the LQ45 Index of the Indonesian Stock Exchange must improve their social and economic performance to improve the company's financial performance.